2001
DOI: 10.1002/1520-6564(200124)11:1<35::aid-hfm3>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Distributed collaboration for engineering design: A review and reappraisal

Abstract: Collaborative manufacturing is aimed to increase the flexibility of design and production processes through multiple organizations pooling strengths on a product‐by‐product basis to create distributed collaborative corporations. These collaborations involve multidisciplinary, geographically dispersed teams of engineers who often communicate only through voice, video, or computer‐mediated interfaces. Utilizing sociotechnical theory as a framework, this article reviews multiple sources of literature on collabora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 29 publications
(108 reference statements)
1
18
0
Order By: Relevance
“…Better solutions arise when diverse perspectives contribute to the creation of artifacts. Those who study collaboration and group work of engineering teams highlight how important interpersonal and social dynamics are to the process (Hacker & Kleiner, 1996;Hammond, Koubek, & Harvey, 2001;Stempfle & BadkeSchaub, 2002) and that the form of communication (inperson or virtually) within a design group matters (Harvey & Koubek, 1998). Stempfle and Badke-Schaub (2002) found that approximately 1/3 of the communication within a group designing collaboratively was aimed at structuring the group's process.…”
Section: Engineering With Peoplementioning
confidence: 99%
See 1 more Smart Citation
“…Better solutions arise when diverse perspectives contribute to the creation of artifacts. Those who study collaboration and group work of engineering teams highlight how important interpersonal and social dynamics are to the process (Hacker & Kleiner, 1996;Hammond, Koubek, & Harvey, 2001;Stempfle & BadkeSchaub, 2002) and that the form of communication (inperson or virtually) within a design group matters (Harvey & Koubek, 1998). Stempfle and Badke-Schaub (2002) found that approximately 1/3 of the communication within a group designing collaboratively was aimed at structuring the group's process.…”
Section: Engineering With Peoplementioning
confidence: 99%
“…In addition to the benefits of having multiple people with diverse perspectives working toward a solution, research highlights how important interpersonal and social dynamics are to engineering (Hacker & Kleiner, 1996;Hammond et al, 2001;Stempfle & Badke-Schaub, 2002) and that engineers' communication, in varying forms (Harvey & Koubek, 1998), and organization are important for effective engineering (Smith & Leong, 1998). Professional engineers communicate with each other throughout the process to ''stay on the same page,'' understand their failures, resolve disagreements and challenges, and reflect on their process (Smith & Leong, 1998;Stempfle & Badke-Schaub, 2002).…”
Section: Engineering With Classmatesmentioning
confidence: 99%
“…Another industryspecific model is introduced by Wang et al (2009a). They have developed a CPD framework for centresatellite system, which can match the collaborative A general approach example is provided by Hammond et al (2001). They have employed a sociotechnical theory to offer a framework within collaborative engineering design context.…”
Section: State-of-the-artmentioning
confidence: 99%
“…Some initial efforts in technology management studies already have started to explore this direction [5]. Socio-technical research claims that considerations of social and technical subsystems within an organization must be optimized jointly and simultaneously for the greatest performances [76].…”
Section: Socio-technical-oriented Approachesmentioning
confidence: 99%
“…For example, in current industry practice, collaboration occurs at all phases and has become an integral part of any engineering project. Although we can recognize the good results of successful collaborations, our ability to re-create the desired collaboration process and train engineers to better collaborate with each other is still very limited [5]. Failure to understand this important activity has led to many harmful consequences and economic losses in the industry.…”
Section: Introductionmentioning
confidence: 99%